(untitled) (Movimenta (ISSN 1984-4298), 2025)
The term Patient and Public Involvement (PPI), derived from the Portuguese “Envolvimento do Paciente e do Público” (EPP), refers to the practice of engaging patients and members of the public in the research process not merely as participants, but as active partners. The core principle of this approach is conducting research “with” or “by” members of the public, rather than “for,” “about,” or “on” them. This practice is grounded in principles that ensure its quality and legitimacy: recognizing public members as equally important within the research team; treating them as equals, with accessible and jargon-free communication; providing the necessary support to enable meaningful contributions; and acting with transparency and accountability in the use of public resources. When these principles are applied, the benefits of involvement become evident: more relevant studies, more sensitive methodologies, greater patient and public engagement, more contextualized interpretations, and, above all, results that truly make a difference in the daily lives of those experiencing the condition under study.